Effects of mixture of CO2 /CH4 as pyrolysis atmosphere on pine wood pyrolysis products. (December 2020) - Xu, Bang; Argyle, Morris D.; Shi, Xiufeng; Goroncy, Alexander K.; Rony, Asif Hasan; Tan, Gang; Fan, Maohong
Abstract: The aim of the present work is to provide a preliminary support and research foundation for developing integrated technology of methane dry reforming and pine wood pyrolysis to produce high value chemicals and fuels. The chemical properties of bio-oil produced by pine wood pyrolysis under traditional N2, H2, CO2, CH4 atmospheres and mixtures of CH4 and CO2 were investigated. Experimental studies were conducted in a fixed bed reactor at a temperature of 500 °C. The results show that pine wood pyrolysis under mixtures of methane and CO2 can promote bio-oil production (0.98% increase) compared with traditional pyrolysis (under N2 ). GC-MS results show that the contents of phenols and sugars in bio-oil decreased, while the amount of alcohols, aldehydes, ketones, and furans increased. NMR spectroscopy provides additional support of the results. Results indicate that bio-oil can be used as a source of value-added chemicals. High proportions of CO were obtained in the gas products from pine wood pyrolysis under CH4 and mixtures of CH4 and CO2 . Finally, a possible reaction pathway of pine wood pyrolysis under mixtures of methane and CO2 is proposed. Methane bi-reforming with CO2 and steam from pine wood pyrolysis could promote the production of high value oxygen-containing chemicals during pine wood pyrolysis under mixtures of CH4 and CO2 . Graphical abstract: Image 1 Highlights: More alcohols, aldehydes, acetones and furans generated by pine wood pyrolysis under mixtures of CH4 and CO2 . High proportions of CO were obtained during pine wood pyrolysis under mixtures of CH4 and CO2 . Methane bi-reforming with CO2 and steam from pine wood can promote the generation of bio-oil during pyrolysis. Postulated possible reaction pathway of pine wood pyrolysis under mixtures of CH4 and CO2 is proposed.